The Drosophila circadian clock is a variably coupled network of multiple peptidergic units - Yao, Z. (Science, 2014)
Daily rhythms in behavior emerge from networks of neurons that express molecular clocks. Drosophila’s clock neuron network consists of a diversity of cell types, yet is modeled as two hierarchically organized groups, one of which serves as a master pacemaker. Here we establish that the fly’s clock neuron network consists of multiple units of independent neuronal oscillators, each unified by its neuropeptide transmitter and mode of coupling to other units. Our work reveals that the circadian clock neuron network is not orchestrated by a small group of master pacemakers but rather consists of multiple independent oscillators, each of which drives rhythms in activity.